A de novo missense mutation in the NC1 domain of type VII collagen leads to dystrophic epidermolysis bullosa - Cheng, Ping; Wu, Yingda; Zhang, Wanlu; Zhang, Yuanyuan; Jia, Weixue; Li, Chengrang (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Dystrophic epidermolysis bullosa (DEB) is a genetic mechanobullous skin disorder that manifests at birth or in early infancy. The hallmarks of DEB are blister formation, skin fragility, and nail dystrophy following minor trauma. The disorder results from mutations in the type VII collagen gene (COL7A1) encoding the type VII collagen protein (C7). C7 is a major component of anchoring fibrils (AFs) [1], which is critical for attachment of the epidermis to the dermis. Dysfunction or loss-of-function of C7 leads to DEB. For instance, the complete loss of C7 causes the Hallopeau-Siemens type of DEB – the most severe phenotype. The inheritance pattern of mutated COL7A1 is either autosomal dominant (DDEB, OMIM 131750) or autosomal recessive (RDEB, OMIM 226600). However, de novo spontaneous mutations of COL7A1 are rarely reported in the population. Herein, we describe a DEB patient with a mild phenotype caused by a de novo missense mutation in the amino-terminal non-collagenous (NC)1 domain of C7.